PERAN ORANG TUA DALAM PERKEMBANGAN PERMAINAN ANAK USIA DINI DI JORONG BUKIT MINDAWA KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Susanti, Laeli; Kasih, Fitria; Yulastri, Weni (Bimbingan dan Konseling, 2013)
The problems studied by the researchers based on a phenomenon in the field was parents who think that kids game is just a wasting of time, parents who do not know the role of a game for children, even parents do not allow their children to play when the boy approached his friend, let children play on their own, parents who have less knowledge in the development of the game, besides the parents are deliberately throwing child play thing. The purpose of this research was to describe: 1) Parentsâ roles in participating for children while playing a game. 2) Parentsâ roles in facilitating childrens games. This research is a descriptive research that produced quantitative data. Population of this research is the overall of parents who have young children (0-6 years), amounting to 101 people. Technique used in sampling is proportional random sampling, in which total sample is 50 people. The instrument was a questionnaire, while for analysis the data used the percentage formula. The results of this research revealed that; 1) Parentsâ roles in participating for children while doing games were categorized well. 2) Parentsâ roles in facilitating childrens games were categorized well. Based on the results of the research, the researcher suggests to the parents in the Bukit Mindawa, Kecamatan Pulau Punjung, Kabupaten Dharmasraya in order to increase its roles in the development of early childhood game.